Feeder mode choice selection behavioural modelling: The case of KTM Komuter, Kuala Lumpur - Bachok, Syahriah; Mohd Zin, Siti Hajar Madina (Malaysian Institute of Planners, 2017)
Transit oriented development propagates the use of feeder services such as buses, taxis and paratransit to support the main rail trunks (Taylor, 1982; Limtanakool et.al, 2006; Alshalalfah & Shalaby, 2007). This paper attempts at explaining the preferences of passengers of a Malaysian rail service towards feeder buses, factors influencing their choices and recommendations to encourage the KTM Komuter passengers to switch mode to feeder services instead of driving their private vehicles to and from stations. Using on-board intercept survey method, some results of 200 samples were analysed for the research. Findings showed that 76% of the passengers did not prefer to use the feeder. As such, the chi-square analysis did not find any socio-demographic factors such as gender, income, level of study, employment types, to be significant in explaining this mode switching behaviour. Some trip characteristics such as vehicle ownership, frequency and length of using the KTM Komuter service also did not significantly influence the passengers' preference in using the feeder bus service. Other factors were then examined, including stations’ characteristics, users’ access and egress behaviours, travel time and distance. Therefore, in order to encourage the KTM Komuter users in using the feeder bus service, several recommendations such as providing an efficient, reliable frequency and catchment areas of feeder bus services were made